Prevalence of ST9 methicillin-resistant Staphylococcus aureus among pigs and pig handlers in Malaysia. - Vasantha Kumari, Neela; Shamsudin, Mariana Nor; Mohd Zafrul , Arif; Van Belkum , Alex; Liew , Y. K.; Rad , Ehsanollah Ghaznavi (American Society for Microbiology, 2009)
Methicillin-resistant Staphylococcus aureus (MRSA) of sequence type 398 (ST398) has frequently been detected in pigs and pig handlers. However, in Malaysia, sampling 360 pigs and 90 pig handlers from 30 farms identified novel ST9-spa type t4358-staphylococcal cassette chromosome mec type V MRSA strains that were found to transiently colonize more than 1% of pigs and 5.5% of pig handlers.